Nationalism Ideology: Critical Discourse Analysis of Joko Widodo's Speech in The Meeting of The Association of Indonesian Village Governments (APDESI) - Kharis Marpurdianto (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
This study aims to analyze the political discourse of Joko Widodo as the President of Indonesia during the meeting of The Association Of Indonesian Village Governments (APDESI). The descriptive qualitative approach was used in this research to gather the data. The data in this study are utterances found in Joko Widodo's speech during the meeting with The Association of Indonesian Village Governments on Tuesday, March 29, 2022. This study uses the identity method of Joko Widodo by using the sociolinguistics method and pragmatic method. The result shows that there are five nationalism ideologies found in the speech of President Joko Widodo, such as the ideology of equality, ideology in unity, ideology in prioritizing the citizen, ideology of national prosperity, and ideology of hard working. Furthermore, this study proves that there is a relationship between language, power, and ideology. President Joko Widodo has the power to choose each word or sentence in his speech and acknowledge the ideology that he carries. Moreover, it makes the audience in the meeting follow and understand President Joko Widodo’s ideology.